Can the peasants speak? Revisiting scotting history in Lewis Grassic Gibbon’s Sunset song - Lopes, Carolina de Pinho Santoro (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2016)
In his novel Sunset Song, Lewis Grassic Gibbon gives voice to the perspective of peasants from the northeast of Scotland, rewriting events of Scottish history in a new light. This paper aims at analyzing the representation of the history of Scotland in the narrative, as well as exploring the influence of the author’s political position and viewpoint on his work. A sympathizer of left-wing ideologies, Gibbon strongly criticizes the elite and praises historical figures whom he considers popular leaders.